PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PT. ASTRA AGRO LESTARI TBK DI BEI PERIODE 2011-2017 - sri Wahyuni Sinaga (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
This study aims to determine the effect of Capital Structure and Profitability on Company Values at PT. Astra Agro Lestari Tbk. The type of research conducted is Causal Associative research which aims to analyze the relationship between one variable with another variable or how a variable affects other variables. The population in this study is the financial statements of PT. Astra Agro Lestari Tbk period 2011-2017.Based on the results of the t test Capital Structure has a significantof 0.144 0.05 which means that the capital structure has a positive and not significant effect on firm value, that the size of the company's debt is not too influential on the value of the company. companies with high debt that can have high corporate value if the debt is managed properly, so the company has a large market value equity Likewise, if the company has a low debt level, it can also have a high corporate value, if the market value equity is large. so that the size of the company's debt has no significant effect on firm valueand Profitability has a sig probability value of 0.018 0.05 which means that profitability has a positive and significant influence on the value of the company at PT.Astra Agro Lestari Tbk, this is due to rapid return on investment and effective. Based on the F test Simultaneously Capital structure and profitability have a value significant 0,040 0.05 so that it can be concluded simultaneously all independent variables Capital Structure and profitability have a positive and significant effect on the dependent variable Corporate Value.             Based on the results of the study, the researchers advise the company to continue to improve and improve financial performance to be able to increase the ability effectively and efficiently to the performance of the company. For investors, pay attention to the level of performance of a company to invest funds. And for other researchers it is recommended to use other ratios as independent variables.